A proposed process map for respiratory gated radiotherapy. Issue 7 (July 2016) - Barry, Amanda; Pembroke, Alan; Neill, Eimear O.; Boychak, Olex
Abstract : Aim: To propose a process map that improves the operational effectiveness and overall process performance for patients undergoing respiratory gated radiotherapy. Introduction: Respiratory motion gating in radiotherapy is performed to manage target or organ motion in the thorax and abdomen that can be influenced by breathing. In order to accurately and reproducibly account for respiratory motion, careful management of the patient before and during a respiratory gated procedure, as well as management of data acquisition methods for treatment planning and treatment delivery purposes are critical. This article integrates respiratory gating practices from the UPMC Whitfield Cancer Centre with respiratory gating methods reported in the literature to propose a process map which can optimally manage this complex technique. Discussion of results: A critical assessment of the various stages in the proposed process will be presented which will highlight improvements in overall process performance. Specific focus will be given to pre-treatment patient preparation, the use of established selection criteria for different respiratory gating methods to improve workflow and data quality for the purpose of radiotherapy treatment planning and treatment delivery. Conclusion: The integration and utilisation of a process map is critical when implementing complex techniques which involve a multidisciplinary team. Using this proposed process map, the UPMC Whitfield Cancer Centre can demonstrate improvements in the overall efficiency of our respiratory motion management process which can lead to a higher quality of service for patients undergoing respiratory motion gated radiotherapy